Epigenetik Mekanizmalar ve Bazı Güncel Çalışmalar - Can, Muhammed İsmail; Aslan, Abdullah (Zonguldak Bülent Ecevit Üniversitesi, 2016)
Uzun yıllardan beri tıp ve biyoloji bilimlerinde, özellikle de genetik alanında, birçok kalıtsal hastalık, yeni keşfedilen kanser türleri ve fonksiyonları tam anlaşılamamış bazı biyolojik sistemlerde birçok çalışma yapılmakta ve yeni teoriler üretilmektedir. Ancak özellikle son yıllarda, bilinen genetik çözümlemelerin yetersiz kaldığı, genetiğin daha ötesindeki mekanizmalarla açıklanabilen birçok olgu mevcuttur ve bunlar epigenetik düzenleme adı altında incelenmektedir. Bu derleme makalesinde, epigenetik alanında yaşanan gelişmeler ve son yıllarda yapılan bazı çalışmalardan bahsedilecektir

For many years, it has been made and many researches and it has been generated new theories in medicine, biology and particularly genetics sciences for many genetic disorders, newly discovered cancer kinds and in some biological systems that their functions are not completely understood. But in recent years, there are many fact that falling short of common genetic analyses and it can explained with further genetics mechanisms and these are examined under the name of epigenetics. In this review article, it will be mentioned from the emerging developments in epigenetics field and some actual studies in recent years.
Epigenetic Mechanisms and Some Recent Studies